ҚАРАҚАЛПАҚ ХАЛЫҚ ӘПСАНАЛАРЫНДА АТ КУЛЬТИ МОТИВИ - Қалбаева, Г.С. (FAN va JAMIYAT, 2017)
The article deals with the analysis of the emergence of the horce cult, its historical basis appeared in the result of diffusion in legends and eposes. The author also reveals the transition of the mythical function of the motive of the horse cult into social and aesthetic function in the result of evolution.